Regenerative Medicine and Diabetes: Targeting the Extracellular Matrix Beyond the Stem Cell Approach and Encapsulation Technology - Peloso, Andrea; Citro, Antonio; Zoro, Tamara; Cobianchi, Lorenzo; Kahler-Quesada, Arianna; Bianchi, Carlo M.; Andres, Axel; Berishvili, Ekaterine; Piemonti, Lorenzo; Berney, Thierry; Toso, Christian; Oldani, Graziano (Frontiers in Endocrinology, 2018)
Abstract According to the Juvenile Diabetes Research Foundation (JDRF), almost 1.25 million people in the United States (US) have type 1 diabetes, which makes them dependent on insulin injections. Nationwide, type 2 diabetes rates have nearly doubled in the past 20 years resulting in more than 29 million American adults with diabetes and another 86 million in a prediabetic state. The International Diabetes Ferderation (IDF) has estimated that there will be almost 650 million adult diabetic patients worldwide at the end of the next 20 years (excluding patients over the age of 80). At this time, pancreas transplantation is the only available cure for selected patients, but it is offered only to a small percentage of them due to organ shortage and the risks linked to immunosuppressive regimes. Currently, exogenous insulin therapy is still considered to be the gold standard when managing diabetes, though stem cell biology is recognized as one of the most promising strategies for restoring endocrine pancreatic function. However, many issues remain to be solved, and there are currently no recognized treatments for diabetes based on stem cells. In addition to stem cell resesarch, several β-cell substitutive therapies have been explored in the recent era, including the use of acellular extracellular matrix scaffolding as a template for cellular seeding, thus providing an empty template to be repopulated with β-cells. Although this bioengineering approach still has to overcome important hurdles in regards to clinical application (including the origin of insulin producing cells as well as immune-related limitations), it could theoretically provide an inexhaustible source of bio-engineered pancreases.